Pricing Efficiency in Major Cattle Auction Centres in the Philippines - Abella, Floyd A. (1989)

(untitled)
The problem of low productivity is the major constraint to the development of the Philippine livestock sector. Contribution from the industry particularly cattle production is considered below potential despite conditions favoring cattle raising in the Philippines. Apart from the technical innovations to encourage cattle raising, an improvement in the marketing system is needed to sustain production. The establishment of livestock auction markets to minimize the defects of the traditional marketing system is believed to be the most feasible short-run modification to effect an efficient marketing of cattle . This study evaluates the pricing efficiency in major cattle auction centres in the Philippines. The univariate residual cross-correlation approach by Haugh (1972 , 1976) and Pierce (1977), and the Sims' (1972) distributed-lag regress ion were used to ascertain Whether the auction centres are integrated in terms of price formation. This was done through the assessment of the nature of causality between prices in the various cattle auctions within and among regions. Time series data an prices consisting of 84 monthly observations were utilized for the purpose. Results showed an inter-dependence among markets, thus, rejecting the null hypothesis of no market integration. The study concludes that government policies geared towards an effective dissemination and monitoring of market information, establishment of more auction markets will enhance the output of the livestock sector.